IMPLEMENTASI KEGIATAN BACA TULIS AL-QUR’AN DI MTS NIZHAMIYAH PLOSO JOMBANG DALAM MENCIPTAKAN GENERASI QUR’ANI - Syahir Naashiruddin (STAI Sufyan Tsauri Majenang, 2023)
To face the swift flow of the times there needs to be a lot of effort in creating a generation that still holds tightly to qur'ani values. Therefore, it is necessary to have activities to read and write the Qur'an to help the younger generation learn about the Qur'an. The implementation of this research was carried out at MTs Nizhamiyah Ploso Jombang, using Qualitative research methods by obtaining data from interview sources of related parties and then analyzed by the author. The purpose of the study was to find out the strategy of MTs Nizhamiyah Ploso in trying to create a generation of qur'ani. The importance of Qur'an-based education and the method of reading and writing the Qur'an at the institution. Mts Nizhamiyah Ploso seeks to produce a generation of qur'ani through the activity of reading and writing the Qur'an. The importance of Qur'anic-based education needs to be instilled in students through the privileges of recitation, tadabbur, memorization, learning and practicing the Qur'an. Al-Qur'an reading and writing activities at Mts Nizhomiyah Ploso use the Tilawati method, and the implementation is divided into several classes according to student capacity. Keyword: Qur'anic Generation. Tilawati Method, Read and Write the Qur'an